THE EFFECTIVENESS OF THE PROBLEM BASED LEARNING MODEL IN IMPROVING LEARNING OUTCOMES OF CLASS VII STUDENTS IN THE SUBJECT OF SOCIAL SCIENCE AT SMP Al FALAH - Parhanudin Nudin; Ismeirita _ (Jurnal Ilmu Pendidikan Ahlussunnah, 2023)
Parhanudin, 2023. "Effectiveness of Using Problem Based Learning Learning Models in Improving Student Learning Outcomes". In Social Sciences class VII subject at Al Falah Middle School, Bekasi City. Thesis, Department of Economic Education, Faculty of Education, Panca Sakti University, Bekasi. Supervised by Mrs. Ismeirita S.Pd., M.Pd.E. This research aims to determine the effectiveness of using the Problem Based Learning model in improving student learning outcomes in Social Sciences subjects for class VII students at Al Falah Middle School, Bekasi City. The method used is pre-experiment using a quantitative approach. The form of one group pretest posttest is an experiment involving 28 students in class VII.4. This research sample was taken using a purposive sampling technique. The instrument in this research uses a test in the form of multiple choice questions, namely pretest and posttest. Based on infreential statistical analysis using the t-test formula, it is known that the tcount value obtained is 4.90 with a frequency of dk= 28-1= 27. At a significance level of 5%, the value of ttable = 1.70 is obtained, so we get tcount > ttable, namely 4 .90 > 1.70. So it can be concluded that the use of the Problem Based Learning Model is effective in improving the Social Sciences learning outcomes of Class VII.4 students at Al Falah Middle School, Bekasi City.